1997
DOI: 10.1128/jvi.71.3.2285-2291.1997
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein H of herpes simplex virus type 1 requires glycoprotein L for transport to the surfaces of insect cells

Abstract: In mammalian cells, formation of heterooligomers consisting of the glycoproteins H and L (gH and gL) of herpes simplex virus type 1 is essential for the cell-to-cell spread of virions and for the penetration of virions into cells. We examined whether formation of gH1/gL1 heterooligomers and cell surface expression of the complex occurs in insect cells. Three recombinant baculoviruses, expressing gL1, gH1, and truncated gH1 (gH1t), which lacks the transmembrane region, were constructed. It was shown that recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 41 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…Milligram amounts of a truncated mammalian form of HSV-1 gH-gL have now been obtained using a stably transfected L-cell line, HL-7, which secretes gHt and gL as a complex. In agreement with what we found for mammalian cells, Westra et al (59) showed that an HSV-1 gHt-gL complex was secreted from insect cells coinfected with recombinant baculoviruses. Spaete et al (53) showed that coexpression of a truncated form of cytomegalovirus (CMV) gH with the UL15 open reading frame gene product (the CMV homolog of HSV gL) results in association of the two proteins and secretion from a transfected cell.…”
Section: Discussionsupporting
confidence: 92%
“…Milligram amounts of a truncated mammalian form of HSV-1 gH-gL have now been obtained using a stably transfected L-cell line, HL-7, which secretes gHt and gL as a complex. In agreement with what we found for mammalian cells, Westra et al (59) showed that an HSV-1 gHt-gL complex was secreted from insect cells coinfected with recombinant baculoviruses. Spaete et al (53) showed that coexpression of a truncated form of cytomegalovirus (CMV) gH with the UL15 open reading frame gene product (the CMV homolog of HSV gL) results in association of the two proteins and secretion from a transfected cell.…”
Section: Discussionsupporting
confidence: 92%
“…These studies suggested that VZV gL acts as chaperone for gH and is not transported to the cell surface or released into the medium (9,10). For HSV-1 and BHV-1, coprocessing and colocalization of gH and gL on the cell surface have been reported (27,32,75). When expressed in the absence of gH, HSV-1 gL was released into the medium (8).…”
mentioning
confidence: 99%
“…42-kDa protein and a 125-kDa protein, respectively (39,40,77). The importance of complex formation with gL for intracellular transport and processing of gH has been analyzed mostly after transient expression (65), expression from recombinant vaccinia viruses in mammalian cells (3,9,10,15,27,32,40,45,77), or expression from recombinant baculovirus in insect cells (22,23,75). These studies suggested that VZV gL acts as chaperone for gH and is not transported to the cell surface or released into the medium (9,10).…”
mentioning
confidence: 99%
“…The gH-gL complex is conserved throughout the herpesviruses, although the nature of the linkage between the two components may differ. In various systems it has been shown that gH requires gL for proper folding and intracellular transport (2,6,32,36,37). In HSV-1, virion localization of gH requires the presence of gL and vice versa (25).…”
mentioning
confidence: 99%